Criminal policy and comparative aspects of private corruption: About its criminalization in Peru - Chanjan Documet, Rafael (2019)
This article addresses the phenomenon of private corruption from a criminal policy perspective. For this, the concept of corruption is analyzed in order to identify if the notes that characterize this phenomenon can be associated with the behaviors classified as corruption in the private activity. Based on this, it is recognized the importance of sanctioning such behaviors due to the serious repercussions they represent for the welfare and development of societies and that have even led the international community to worry about fostering their persecution. Also, the main systems that have been adopted at the international level in the task of sanctioning private corruption behaviors are presented and explains what is the model adopted by Peruvian legislation.